2010
DOI: 10.15835/nsb234710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genotype, Explant and Hormonal Concentration on in Vitro Response of Eggplant

Abstract: Three wild relatives Solanum: S. trilobatum L. (P1), S. indicum L. (P2), S. surattense Burm F. (P3) and four cultivars of S. melongena L.: 'Pusa Kranthi' (P4), 'Pusa purple long' (P5), 'Pusa purple cluster' (P6) and 'Green round' (P7) were evaluated for their callus induction frequency, total callus quantity, embryogenic callus quantity and plant regeneration ability. The present experiment revealed that in vitro response was significantly affected by the genotype, hormonal concentration and age of the explant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…According to Gahan and George (2008), the plant genotype has a marked effect on the behavior of plant tissues, so it is possible to obtain plants with improved performance in all aspects of culture. In the case of eggplant seeds, for example, seven genotypes tested showed variation in their in vitro responses, with increased productivity of some specific genotypes (CHAKRAVARTHI et al 2010). This relationship between genotypes and in vitro responsiveness is well documented for several commercial cultivars such as maize, barley and rice (as reviewed by XOCONOSTLE-CÁZARES, 2011).…”
Section: Upgma Algorithmmentioning
confidence: 90%
See 3 more Smart Citations
“…According to Gahan and George (2008), the plant genotype has a marked effect on the behavior of plant tissues, so it is possible to obtain plants with improved performance in all aspects of culture. In the case of eggplant seeds, for example, seven genotypes tested showed variation in their in vitro responses, with increased productivity of some specific genotypes (CHAKRAVARTHI et al 2010). This relationship between genotypes and in vitro responsiveness is well documented for several commercial cultivars such as maize, barley and rice (as reviewed by XOCONOSTLE-CÁZARES, 2011).…”
Section: Upgma Algorithmmentioning
confidence: 90%
“…According to Chakravarthi et al (2010), several intrinsic and extrinsic factors influence tissue culture responses, especially the nature and age of the explant, genotype, type and concentration of growth regulators. Different varieties and plant genotypes may differ in their requirements for growth regulators, particularly auxin, in the culture medium .…”
Section: Upgma Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, direct regeneration was observed during the course of callus developmenton media C3 ( Figure 3A). Chkravarthi et al [44] also found that the concentrations of BAP ranging from 0.5-3.5 mg L -1 induced direct regeneration instead of callus induction. Whereas the medium C12 supplemented with 2.0 mg L -1 NAA + 0.5 mg L -1 BAP was found to be quite effective for the proliferation of callus as compared to other media types ( Figure 3B-C).…”
Section: Callus Induction Percentagementioning
confidence: 96%